Poverty Reduction Through the ZISWAF Program The Sinergi Foundation Village Barn in Cibaeud Village Tasikmalaya District - Faqih Adam; Nida Nabila; Nur Hidayati (Universitas Pendidikan Indonesia, 2018)
The Ziswaf problem in contemporary times is not only in the collection of funds, but the more urgent matter to consider is the strategy of the ziswaf distribution itself. This study aims to analyze the impact of the village bam program in reducing the poverty of mustahik households, both in terms of material and spiritual aspects. This study uses primary data with interviews through questionnaires in the village of Cibaeud, Lembong Jaya Village, Ciganlontang District, Tasikmalaya, as many as 69 respondents from the population of 120 households. The CIBEST model by Beik and Arsyianti was used as ananysis tool. There are 42% of people experiencing a change in welfare level, 33% decrease in material poverty rates, 5,7% decrease in spiritual poverty rates, and 2,9% decrease in absolute poverty rates. The concept of the Sinergi Foundation village bam program was able to break the chain of middlemen (Ijon) distribution by collecting agricultural products at the Sinergi Foundation village granary institution to be marketed directly